Serum and urine eosinophil-derived neurotoxin (EDN) levels predict biologic response in severe asthma - Yu Ri Kang, MD; Hyunkyoung Kim, MS, MPH; Chae Eun Lee, BS; Jae-Woo Jung, MD, PhD; Ji-Yong Moon, MD, PhD; So Young Park, MD, MS; Sae-Hoon Kim, MD, PhD; Min-Suk Yang, MD, PhD; Byung Keun Kim, MD, PhD; Jae-Woo Kwon, MD, PhD; Hye-Kyung Park, MD, PhD; Young-Hee Nam, MD, PhD; et al. (World Allergy Organization Journal)
Background: Eosinophils are crucial in allergic inflammation, and their correlation with asthma severity has made them a focal point in predicting treatment outcomes. Blood eosinophil count is a commonly utilized marker. However, its limitations have prompted alternative biomarker exploration, such as eosinophil-derived neurotoxin (EDN). Objective: This research was conducted over 24 weeks on 56 patients with severe asthma treated with mepolizumab, reslizumab, and dupilumab. We aimed to evaluate the clinical significance of blood eosinophil count and their potential, including those of blood EDN levels and urine EDN values as biomarkers for predicting treatment response. Methods: The analysis encompassed examining correlations between biomarkers and clinical features, including exacerbation rates and lung function, through ELISA assays and subsequent statistical analyses. The study protocol is registered at ClinicalTrials.gov (NCT05164939). Results: The findings underscore strong correlations between serum EDN levels, blood eosinophil counts, and treatment responses, with EDN demonstrating comparable predictive capabilities to blood eosinophil counts to determine treatment responses. Different biologics exhibited varying efficacy regarding baseline eosinophil counts and EDN levels. Conclusions: Blood eosinophil counts and EDN levels show potential as predictive markers for treatment responses in patients with severe asthma undergoing biologic therapies. However, further comprehensive studies are warranted to enhance the reliability and applicability of EDN as an effective asthma treatment biomarker.